2018
DOI: 10.1364/oe.26.013020
|View full text |Cite
|
Sign up to set email alerts
|

Compositional redistribution in CaO–Al2O3–SiO2glass induced by the migration of a steel microsphere due to continuous-wave-laser irradiation

Abstract: A high-power continuous-wave (CW) laser was used to move a steel microsphere through a CaO-AlO-SiO glass block at room temperature along a trajectory toward the laser source. A compositional analysis revealed that the CaO concentration in the glass decreased at the center of the microsphere's trajectory but increased in the area adjacent to it; the SiO concentration showed an opposite trend while the AlO concentration did not change. Further, the compositional difference between the center and the area adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…39) Kishi et al reported the Soret effect induced by the continuous-wave-laser irradiation to a steel microsphere inside a 30CaO10Al 2 O 3 60SiO 2 (mol %) glass. 40)…”
Section: Soret Effect Induced By Laser-local Heatingmentioning
confidence: 99%
“…39) Kishi et al reported the Soret effect induced by the continuous-wave-laser irradiation to a steel microsphere inside a 30CaO10Al 2 O 3 60SiO 2 (mol %) glass. 40)…”
Section: Soret Effect Induced By Laser-local Heatingmentioning
confidence: 99%